UTILIZATION OF GEOGEBRA IN ENHANCING HIGH SCHOOL STUDENTS’ MATHEMATICAL REASONING ABILITY - Egi Anjeliani Devi; Nuralam Syamsuddin (Jurnal Numeracy, 2026)
Students’ low mathematical reasoning skills, particularly regarding abstract concepts such Students’ mathematical reasoning ability in the topic of tangent lines to a circle remains relatively low, particularly in integrating geometric and algebraic concepts. This indicates limitations in students’ conceptual understanding, which may be influenced by the use of conventional teaching methods with minimal visualization. This study aims to examine the effectiveness of GeoGebra in improving high school students’ mathematical reasoning ability. This study employed a quasi-experimental method with a pretest–posttest control group design involving 44 eleventh-grade students’ at SMAN 5 Banda Aceh. The data were analyzed using the Method of Successive Interval (MSI) and an independent sample t-test. The results showed that the experimental group achieved a higher average post-test score (13.13) compared to the control group (11.04). The calculated t-value (5.13) exceeded the critical t-value (2.018), indicating a significant difference between the two groups. Therefore, the use of GeoGebra was proven to be effective in improving students’ mathematical reasoning ability compared to conventional methods. These findings confirm that the integration of technology in geometry learning can create a more interactive learning environment and support the development of students’ logical thinking skills.